Car drivers with dementia: Different complications due to different etiologies?. (2nd January 2016) - Piersma, Dafne; de Waard, Dick; Davidse, Ragnhild; Tucha, Oliver; Brouwer, Wiebo
ABSTRACT: Objective: Older drivers with dementia are an at-risk group for unsafe driving. However, dementia refers to various etiologies and the question is whether dementias of different etiology have similar effects on driving ability. Methods: The literature on the effects of dementia of various etiologies on driving ability is reviewed. Studies addressing dementia etiologies and driving were identified through PubMed, PsychINFO, and Google Scholar. Results and Conclusions: Early symptoms and prognoses differ between dementias of different etiology. Therefore, different etiologies may represent different likelihoods with regard to fitness to drive. Moreover, dementia etiologies could indicate the type of driving problems that can be expected to occur. However, there is a great lack of data and knowledge about the effects of almost all etiologies of dementia on driving. One could hypothesize that patients with Alzheimer's disease may well suffer from strategic difficulties such as finding a route, whereas patients with frontotemporal dementia are more inclined to make tactical-level errors because of impaired hazard perception. Patients with other dementia etiologies involving motor symptoms may suffer from problems on the operational level. Still, the effects of various etiologies of dementias on driving have thus far not been studied thoroughly. For the detection of driving difficulties in patients with dementia, structured interviews with patients but also their family members appear crucial. Neuropsychological assessment could support the identification of cognitive impairments. The impact of such impairments on driving could also be investigated in a driving simulator. In a driving simulator, strengths and weaknesses in driving behavior can be observed. With this knowledge, patients can be advised appropriately about their fitness to drive and options for support in driving (e.g., compensation techniques, car adaptations). However, as long as no valid, reliable, and widely accepted test battery is available for the assessment of fitness to drive, costly on-road test rides are inevitable. The development of a fitness-to-drive test battery for patients with dementia could provide an alternative for these on-road test rides, on condition that differences between dementia etiologies are taken into consideration.